Pengaruh Media Ludo Word Game (Lwg) Untuk Meningkatkan Kosakata Bagi Anak Tunarungu Kelas Iv Di Slb N 1 Padang Panjang - Anna Tovni Sonia; Armaini Armaini (Universitas Negeri Padang, 2018)
This research was motivated by the problems that the researcher found in class V SLB N 1 Padang Panjang with the number of children consist of five pupil. At this, the are school are children with hearing impairment who have not been able to master the vocabulary well. The delivery of learning that uses less attractive media makes children less enthusiastic in teaching and learning processes. The study aims to prove effectiveness of ludo word game media to improve vocabulary for children with hearing impairment class V in SLB N 1 Padang panjang.This research uses experimental method with form pre-experimental design with type one group pretest-posttest design. Subject of five children given pretest after that given treatment whit Ludo Word Game Media and finally given protest for see the child’s ability after being given treatment. Value of pretest and posttes processed and compared using the test Mann Whitney for test the research hypothesis.The results of the work process of the five students in vocabulary after being analyzed by looking at the average at pretest is 44% while for posttetst there is an increase that is 70%. The data was processed using the Mann Whitney test. Uhit = 3 and Utab = 2 were obtained with n = 5 at 95% significance level and α = 0.05. The alternative hypothesis was accepted because of Uhit> Utab, so it was proven that Ludo Word Game Media was effective to improve Vocabulary For Children With Hearing Impairment In Class V SLB N 1 Padang Panjang.